EFL Learners’ Perspectives in Implementing Digital Annotation to Foster Critical Reading Skills - Afriyeni, Yeni; Maspufah; Zuriati, Diana; Rosmala (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Critical reading requires advanced cognitive skills to evaluate, interpret, and analyse texts effectively. However, mastering critical reading can be challenging, especially for learners, due to factors such as vocabulary gaps, cultural differences, and diverse educational backgrounds. This study aimed to explore learners' perspectives on the implementation of digital annotation in enhancing their critical reading skills. This was descriptive qualitative research. Total sampling technique was applied in choosing the sample which involving sixteen eleventh-grade students from a private Islamic senior high school. The data were collected by using a questionnaire developed through Google Forms and it were analysed by reducing, displaying, and drawing conclusion which adopted from a three-step qualitative data analysis.The findings revealed that the use of digital annotation tools was perceived positively by students, as it facilitated better comprehension of reading materials, eased the acquisition of new vocabulary, encouraged critical thinking, and supported the generation of new ideas. Nevertheless, several challenges were identified, such as difficulty in articulating critical thoughts in writing, challenges in interpreting feedback notes, unstable internet connectivity, limited digital skills and supporting resources, digital distractions, and confusion caused by excessive annotations from multiple perspectives. In conclusion, learners had a generally positive attitude toward digital annotation despite facing implementation barriers. Therefore, educators are encouraged to integrate digital annotation thoughtfully, considering students’ digital literacy, technological access, and regional educational contexts to ensure effective and inclusive learning.